Variation in ecological risk at three Nevada gold mines over a ten year post-closure period - Robinson, EA (Mine Closure 2012: Proceedings of the Seventh International Conference on Mine Closure, 2012)
This case study considers screening-level ecological risk assessment as a complementary technique to traditional rehabilitation monitoring methods for growth and productivity by evaluating the change in ecological risk from heap leach draindown over time. Available data from three Nevada gold mines were examined for a ten year post-closure period. The study found that variation in ecological risk can be used to plan adaptive management approaches in response to changing risks and liabilities. However, the likelihood of implementing new management approaches post-closure remains in question.